RISK BASED TECHNO ECONOMIC ANALYSIS OF COILED TUBING PROJECT OF INDONESIA OFFSHORE FIELD - F Farizal; Azhar Maulana (Center for Study and Journal Management FTI UMI, 2022)
In oil and gas industry, coiled tubing is well intervention services with the objective to increase the well production. However, utilizing this technology is not free. It is important to analyze the coiled tubing project feasibility to ensure its economic value. This study used Net Present Value (NPV) method that highly influenced by the discount rate used. In addition to Weighted Average Cost of Capital (WACC) method that commonly uses to determine the rate, to accommodate uncertainty and risk associated with the project, Triangular Fuzzy Number (TFN) and Risk Adjusted Discount Rate (RADR) are also used. As the results the estimated discount rates were 13.61%, 13.53% and 16.00% for WACC, TFN, and RADR, respectively. All estimated discount rates gave positive NPVs. This means the coiled tubing project is feasible and profitable.